Surface Dosimetry of Ultraviolet Germicidal Irradiation Using a Colorimetric Technique. Issue 5 (22nd February 2021) - Neu, Dylan T; Mead, Kenneth R; McClelland, Tia L; Lindsley, William G; Martin, Stephen B; Heil, Graeham; See, Mitch; Feng, H Amy
Abstract: Ultraviolet germicidal irradiation uses ultraviolet C (UV-C) energy to disinfect surfaces in clinical settings. Verifying that the doses of UV-C energy received by surfaces are adequate for proper disinfection levels can be difficult and expensive. Our study aimed to test commercially available colorimetric labels, sensitive to UV-C energy, and compare their precision with an accepted radiometric technique. The color-changing labels were found to predictably change color in a dose-dependent manner that would allow them to act as a qualitative alternative to radiometry when determining the minimum UV-C energy dosage received at surfaces. If deployed using careful protective techniques to avoid unintentional exposure to sunlight or other light sources, the use of colorimetric labels could provide inexpensive, easy, and accurate verification of effective UV-C dosing in clinical spaces.